Investigation of a Solar Polygeneration System for a Multi-Storey Residential Building-Dynamic Simulation and Performance Analysis - Missoum, Mohammed; Loukarfi, Larbi (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
In the present study, the performance of a novel configuration of a solar polygeneration system for a multi-family residential building is investigated using dynamic simulation models. The system consists in Building Integrated PhotoVoltaic/Thermal (BIPVT) collectors, a water-to-water reversible heat pump and an adsorption chiller. The solar system will ensure space heating in winter, space cooling in summer and domestic hot water and electricity all over the year for a multi-storey building located in Algiers (Algeria). In the case of insufficient solar energy, the system is equipped with a gas-fired heater for auxiliary heat production, whereas the auxiliary electricity is supplied by the national grid. First, the simulation models of the solar system components and the building were described and developed in TRNSYS environment. Then, an energy-economic model based on the calculation of the primary energy consumption, the primary energy saving, the simple payback period and the electrical and thermal solar fractions, was carried-out. Finally, the system performance in terms of daily, monthly and yearly results was investigated and compared to the performance of a conventional energy system commonly used in Algerian buildings. The simulation results indicate that the solar collectors have the potential to cover more than 56% and 72% of the yearly heat and electricity requirements, respectively. The total primary energy saving achieved by the solar system with respect to the conventional one is 37.1 MWh/y, which represents 39% of the energy consumption of the conventional system. However, the economic feasibility of proposed solar system is difficult to be achieved due to the high initial cost of the solar collectors. Indeed, the obtained simple payback period is 55.40 years. Moreover, a sensitivity analysis has been performed aiming at studying the effect of various technical and economical parameters on the system performance. The analysis shows that the energetic as well as economic performances of the system are strongly influenced by the photovoltaic/thermal filed area, the system cost and the unitary cost of electricity. The system becomes economically profitable when the system cost is 400 €/m² and the electricity cost is 0.12 €/kWh. Additionally, the system performance is better in climate conditions where solar potential and building energy requirements are important.